Asjraq Magazine 1925–1928: Minangkabau Women and Modernity - Al-Insyi, Salsabila Yumna; Samry, Wannofri (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This research aims to examine the progression of Minangkabau women during the 20th century as reflected through modern education represented in the women's press. As historical research, this research uses the historical method, which includes heuristics, source criticism, interpretation, and historiography. The focus is on the progress and development of Minangkabau women as represented in Asjraq magazine, published in Padang, West Sumatra. Asjraq was one of the women’s magazines actively advocating for the advancement and empowerment of Minangkabau women. The exploration of women’s ideas consistently colored every issue of Asjraq, presenting concepts that contributed to redefining women’s roles in an evolving modern world. These ideas also provoked reactions from Minangkabau society. Elements and expressions of modernity found in Asjraq include education, participation in associations and mass media, as well as artistic expression.